Tingkat Kepuasan Pelaku Usaha terhadap Lembaga Swadaya Masyarakat di dalam Penegakan Hukum di Republik Indonesia - Pandapotan Siahaan, David; P. Silaen, August (Journal of Comprehensive Science, 2025)
This research aims to measure the level of business actors' satisfaction with the role of non-governmental organizations (NGOs) in law enforcement in the Republic of Indonesia. As a non-governmental entity, NGOs have an important function in supporting the creation of justice and legal certainty, which has an impact on the business environment. Data was collected through a survey of business actors from various sectors, which was evaluated based on their perceptions of the effectiveness, transparency, and contributions of NGOs in law enforcement. The research methodology uses a quantitative approach with descriptive and regression analysis to determine the factors that influence the satisfaction of business actors. The results of the study show that the level of business actor satisfaction varies, depending on the business sector and the involvement of NGOs in relevant legal advocacy. The factors of transparency and accountability of NGOs were found to have a significant influence on the level of satisfaction. The conclusions of this study provide insights for NGOs to enhance their role in creating a conducive business climate and strengthening collaboration with business actors. Recommendations are also made to improve communication and strengthen NGO accountability in the future.